The Essential Book of Home Improvement Techniques : All You Need to Make the Home You've Got the One You Want - Holloway, David, 1944- ; McGowan, John and Lawrence, Mike; Consultant Editor Wilkins, Tony (London Marshall Publishing, 1999)
A combination of directory and step-by-step instructions, this manual includes all kinds of help and advice on different home improvement techniques. It explains which technique is required for a particular job, how long it will take and what tools will be needed.
Include Color Illustration and Index
Keywords: Dwellings--Remodeling